2020
DOI: 10.1002/eat.23270
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder psychopathology in adults and adolescents with anorexia nervosa: A network approach

Abstract: Objective: The aim of this study was to assess and compare eating disorder feature networks in adult and adolescent patients with anorexia nervosa. Methods: Patients seeking treatment for anorexia nervosa in inpatient and outpatient settings were consecutively recruited from Body mass index was measured, and each patient completed the Eating Disorder Examination Questionnaire. Results: The sample comprised 547 adolescent and 724 adult patients with anorexia nervosa. Network analysis showed that in both adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 40 publications
10
58
0
Order By: Relevance
“…68 Support for the affirmation that eating-disorder psychopathology is essentially the same in all ages comes from the observation that, although some of its features (ie, binge-eating episodes, self-induced vomiting, laxative and diuretic misuse) are more frequent in adults than in adolescents, they are also reported by a many adolescents with eating disorders. 72 This observation explains why, as shown in Table I, all of the main feeding and eating-disorder diagnostic categories in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) 73 are represented in both adolescent and adult patients, with higher prevalences of BN in adults and of atypical AN in adolescents. Another finding suggesting that eating-disorder psychopathology is similar in adults and adolescents comes from a study that used network analysis for assessing data from 547 adolescent and 724 adult patients with AN 72 ; that study found that desiring weight loss, and shape and weight overvaluation and concern are central nodes with strong connections to all the other eatingdisorder variables investigated in both adult and adolescent networks (Figure 2).…”
Section: Distinctive Psychopathology Shared By Adults and Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations
“…68 Support for the affirmation that eating-disorder psychopathology is essentially the same in all ages comes from the observation that, although some of its features (ie, binge-eating episodes, self-induced vomiting, laxative and diuretic misuse) are more frequent in adults than in adolescents, they are also reported by a many adolescents with eating disorders. 72 This observation explains why, as shown in Table I, all of the main feeding and eating-disorder diagnostic categories in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) 73 are represented in both adolescent and adult patients, with higher prevalences of BN in adults and of atypical AN in adolescents. Another finding suggesting that eating-disorder psychopathology is similar in adults and adolescents comes from a study that used network analysis for assessing data from 547 adolescent and 724 adult patients with AN 72 ; that study found that desiring weight loss, and shape and weight overvaluation and concern are central nodes with strong connections to all the other eatingdisorder variables investigated in both adult and adolescent networks (Figure 2).…”
Section: Distinctive Psychopathology Shared By Adults and Adolescentsmentioning
confidence: 99%
“…72 This observation explains why, as shown in Table I, all of the main feeding and eating-disorder diagnostic categories in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) 73 are represented in both adolescent and adult patients, with higher prevalences of BN in adults and of atypical AN in adolescents. Another finding suggesting that eating-disorder psychopathology is similar in adults and adolescents comes from a study that used network analysis for assessing data from 547 adolescent and 724 adult patients with AN 72 ; that study found that desiring weight loss, and shape and weight overvaluation and concern are central nodes with strong connections to all the other eatingdisorder variables investigated in both adult and adolescent networks (Figure 2). This finding indicates that overvaluation of shape and weight and additional indicators of shape and weight concern are central features in the psychopathology in both adults and adolescents with AN.…”
Section: Distinctive Psychopathology Shared By Adults and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of the NA approach over the past decade has provided a theoretical framework that was adopted to identify the central symptoms of different psychiatric disorders, such as bipolar disorder [15], depression [16], obsessive compulsive disorder [17] and schizophrenia [18]. More recently, researchers in the field of eating disorders have applied NA to examine the symptoms of anorexia nervosa [19][20][21][22] and bulimia nervosa [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The development of network approach over the past decade has provided a theoretical framework that was adopted to identify the central symptoms of different psychiatric disorders such as bipolar disorder [15], depression [16], obsessive compulsive disorder [17], or schizophrenia [18]. More recently, researchers in the eld of eating disorders (EDs) have applied NA to examine the symptoms of Anorexia Nervosa [19][20][21][22] and Bulimia Nervosa [23][24][25].…”
Section: Introductionmentioning
confidence: 99%